Cu-ZnO Nanostructures Synthesis and Characterization - Saif T. Abdulredha; Nadia A. Abdulrahman (Iraqi Journal of Science, 2021)
5wt% copper doped zinc oxide (Cu-ZnO) nanostructures were prepared via the hydrothermal technique at different temperatures of 70, 100, 130, 160 and 190oC. UV spectroscopy, FE-SEM microscopy, XRD crystallography, and EDS measurements were used for nanostructure characterization. UV spectroscopy indicated a red shift for the absorption peaks, and hence a blue shift for the energy gap values, as temperature increased from 70 to 190oC. FE-SEM microscopy showed an increase in the average lengths and diameters of the nanostructures following a similar increase in temperature. XRD crystallography indicated decent structural patterns for Cu-ZnO nanostructures with an increase in crystallite size upon temperature increase. Interestingly, three unprecedented extra indices appeared in the structural pattern at 190oC, which might indicate a configuration of hexagonal crystallite with three extra planes. EDS measurements indicated the sole presence of Cu, Zn and O.